BMC Medical Education - SpringerLink (Online service) (London : BioMed Central : Imprint: BioMed Central.)
BMC Medical Education is an open access journal publishing original peer-reviewed research articles in relation to the training of healthcare professionals, including undergraduate, postgraduate, and continuing education. The journal has a special focus on curriculum development, evaluations of performance, assessment of training needs and evidence-based medicine.
Keywords: Medical ethics; Medical education; Medical Education; Theory of Medicine/Bioethics.